2013
DOI: 10.1097/01.naj.0000431922.47547.eb
|View full text |Cite
|
Sign up to set email alerts
|

A Project to Reengineer Discharges Reduces 30-Day Readmission Rates

Abstract: A Texas hospital achieves improvement in its readmission rate by implementing Project RED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Despite moves toward earlier discharges, there is increasing pressure from public and private payers to reduce readmissions for an expanding number of admission diagnoses [ 15 , 16 ]. The transition from in-hospital care to home care, and the management of home care, are increasingly recognized as important factors that can influence the rate of readmissions [ 17 ]. Early recognition of complications may allow outpatient management in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Despite moves toward earlier discharges, there is increasing pressure from public and private payers to reduce readmissions for an expanding number of admission diagnoses [ 15 , 16 ]. The transition from in-hospital care to home care, and the management of home care, are increasingly recognized as important factors that can influence the rate of readmissions [ 17 ]. Early recognition of complications may allow outpatient management in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Many have focused on methods that can be grouped into predischarge, postdischarge, and bridging strategies. 16 Commonly, the focus is on patient education, timely follow-up, and coordination with both primary care physicians and skilled nursing care, [16][17][18] and showed promising early results. Another recent report showed that a 24-hour consultation phone service for TJA patients can reduce the number of ED visits in the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial of over 700 patients, patients assigned to Project RED (versus usual care) had a significantly lower rate of emergency department visits and hospitalizations within 30 days (incidence rate ratio 0.7, p=0.009) 56 Implementation of Project RED components in another setting was associated with a reduction of readmission rates (relative reduction: 36% at 30 days, compared to historical data). 66 …”
Section: Evidence-based Programs To Reduce Hospital Readmissionsmentioning
confidence: 99%